2014
DOI: 10.1016/j.neurobiolaging.2014.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Genetic architecture of ALS in Sardinia

Abstract: Conserved populations, such as Sardinians, displaying elevated rates of familial or sporadic ALS provide unique information on the genetics of the disease. Our aim was to describe the genetic profile of a consecutive series of ALS patients of Sardinian ancestry. All ALS patients of Sardinian ancestry, identified between 2008 and 2013 through the ITALSGEN consortium, were eligible to be included in the study. Patients and controls underwent the analysis of TARDBP, C9ORF72, SOD1, and FUS genes. Genetic mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 25 publications
4
53
0
Order By: Relevance
“…Regarding the studies reporting TARDBP mutations, sensitivity analysis revealed that when the study by Borghero et al 11 was omitted, the heterogeneity greatly reduced in studies either in patients with FALS (I 2 reduced to 48%) or patients with SALS (I 2 reduced to 67%), suggesting that this study may cause the instability of the results.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Regarding the studies reporting TARDBP mutations, sensitivity analysis revealed that when the study by Borghero et al 11 was omitted, the heterogeneity greatly reduced in studies either in patients with FALS (I 2 reduced to 48%) or patients with SALS (I 2 reduced to 67%), suggesting that this study may cause the instability of the results.…”
Section: Resultsmentioning
confidence: 98%
“…Interestingly, 16 patients with FALS and 2 patients with SALS harbouring double mutations have been identified in 5 out of 17 studies screening these four genes 2–7 11 16–25. Fifteen patients harboured C9orf72 repeated expansion in combination with the SOD1 , TARDBP or FUS mutation,4 11 16–18 while three patients had double mutations in the TARDBP gene 4 11.…”
Section: Discussionmentioning
confidence: 99%
“…We approached this question by comparing baseline demographic and clinical features of C9Pos to C9Neg patients from a cohort of 781 patients with ALS to determine whether these 2 groups are clinically distinct, adding to published reports from European cohorts. 21,22 This was a clinic-based series of patients with ALS, which allowed us to avoid bias in patient selection. All patients at the Emory ALS Center are asked to donate DNA for research purposes, and thus the only criteria for inclusion were the diagnosis of ALS and the consent to donate blood for research.…”
Section: Demographic and Clinical Information Acquisitionmentioning
confidence: 99%
“…Our finding of reduced overall survival in our C9Pos population compared to C9Neg patients is consistent with the published experience from other C9Pos cohorts. 3,4,8,22,23 In addition, we used a Cox proportional hazards model to determine the influence of variables other than the C9 mutation, such as Figure 1 Flowchart of family history of amyotrophic lateral sclerosis (ALS) in screened cohort A total of 781 cases were screened for the C9orf72 expansion. Of those 781, 90 cases had a known family history of ALS, while 691 had no known family history of ALS.…”
Section: Demographic and Clinical Information Acquisitionmentioning
confidence: 99%
“…Further studies are needed to determine if the co-occurrence of ATXN2 and C9orf72 expansions could influence age at onset or survival in addition to the ALS/FTD phenotype. The C9orf72 expansion has also been described in association with TARDBP, FUS, and SOD1 mutations [109][110][111][112][113][114][115][116] in patients with ALS, with PGRN, MAPT, PSEN-2, and SQSTM1 mutations in FTD patients [75,[117][118][119][120], and with variants in other minor genes, such as ANG, PRPH, OPTN, DAO, UBQLN2, VAPB, CHMP2B, SETX, ALS2, SPG11, and DCTN1 [20,[110][111][112][113]121]. Double mutations have also been described in patients without C9orf72 mutations.…”
mentioning
confidence: 99%